1987
DOI: 10.1038/bjc.1987.304
|View full text |Cite
|
Sign up to set email alerts
|

Cancers of the upper alimentary and respiratory tracts in Bombay, India: A study of incidence over two decades

Abstract: Summary Cancers of tongue, oropharynx and larynx in males have registered a decline in incidence over the last two decades in Bombay. This decline has been shown to be a cohort effect. A synoptic measure of risk in each birth cohort, obtained by estimating site-specific cumulative incidence rate over an appropriate age range, was found useful in assessing the risk differential in successive birth cohorts.The changing pattern in incidence of cancers at several sites viz., tongue, oropharynx, and larynx, where b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The latest data show an incidence rate of 6.5 per 100 000 per annum from 1988-1992 (Parkin et al, 1997). In a study between 1964, Jayant and Yeole (1987 confirmed that the incidence of tongue cancer in Bombay is falling. Hamada et al (1991) showed that tongue cancer contributed 44.4% of all cancers of the mouth and oropharynx in males in Bombay.…”
Section: Asia (A) Malementioning
confidence: 97%
See 1 more Smart Citation
“…The latest data show an incidence rate of 6.5 per 100 000 per annum from 1988-1992 (Parkin et al, 1997). In a study between 1964, Jayant and Yeole (1987 confirmed that the incidence of tongue cancer in Bombay is falling. Hamada et al (1991) showed that tongue cancer contributed 44.4% of all cancers of the mouth and oropharynx in males in Bombay.…”
Section: Asia (A) Malementioning
confidence: 97%
“…This converts to 57.0% of all intraoral cancers. The elevated rates in India are commonly linked to betelquid chewing habits, especially if tobacco is a component (Boyle et al, 1990;Daftary et al, 1992;Gupta and Nandakumar, 1999;Jayant and Yeole, 1987;Sankaranarayanan et al, 1989;Smith, 1973Smith, , 1989. In this context, it is also interesting to note that although the rate of tongue cancer in Singapore is low, it is elevated in the Indian sub-population and has been for the past two decades.…”
Section: Asia (A) Malementioning
confidence: 99%
“…Once again, tobacco and betel-quid habits are implicated as the primary aetiological agents for the consistently high rates seen in India (Sankaranarayanan, 1990;Daftary et al, 1992), although Sankaranarayanan et al (1989) proposed that other factors (such as immune deficiency, viruses, genetic and dietary factors) are involved in the development of oral cancer in patients under 30 years of age. Some researchers (Jayant and Yeole, 1987;Coleman et al, 1993) have reported a plateauing in the incidence rates of mouth cancer in India from the 1960s to the mid-1980s, but they remain among the highest in the world. In contrast to India, the risk of mouth cancer in Japan is low, but the rate has increased dramatically.…”
Section: Asiamentioning
confidence: 99%
“…buccal mucosa, esophagus, tongue, larynx, hypopharynx and oropharynx. Jayant and Yeole (1987) reported a change in bidi smoking habit in the population of Mumbai, while analyzing the declining trends of cancer of tongue, oropharynx and larynx in men. However, they also suggested an emerging cancer pattern in the country at variance with the pattern expected from the current cancer trends in Mumbai.…”
Section: Observations and Resultsmentioning
confidence: 99%